Options markets - John C. Cox; Mark Rubinstein (New Jersey Prentice Hall, 1985)
This exploration of options markets blends institutional practice with theoretical research. Discusses theoretical models for the valuation of options and outlines trading strategies for puts and calls.
Donated by: Anvar Hodjaev